Management Of Residual Pituitary Adenoma Patient With Manifestation of Acromegaly and Hyperprolactinemia - Khoirotul Ummah; Soebagijo Adi (Universitas Airlangga, 2021)
Pituitary adenoma is one of intracranial tumors that grows and develops in the pituitary gland which plays a role in regulating the hormonal balance in the body. Most pituitary adenomas are benign and do not spread to other organs. Pituitary adenoma can be classified based on radiological features, tumor size and the type of hormone produced. There are several ways to establish of diagnosis of pituitary adenoma, in addition to recognizing the symptoms and clinical signs are hormonal function tests and imaging. The surgery is the first medical actions. The postoperative recovery rate reached 90% in relatively benign cases and tumor recurrence rate is 5-10% depending on the size of the tumor, the stage of the tumor during surgery, experience of neurosurgical. A woman, 46 years old referred to Soetomo Hospital from Soebandi Jember Hospital for treatment the recurrent adenoma pituitary with complains of headache, double-vision and changing shape of his face, his enlarged lips and nose. Patient was diagnosed based on head CT scan and already had surgery on January, 2015. The head MRI evaluated post surgery was still a residual mass from the previous tumor. 3 monts after surgery no complains any more. The complains reappear at the end of 2017. The head CT scan on January, 8, 2017, size tumor: 1.2 cm x 1.8 cm. The head MRI results on December, 20, 2017 size tumor : size 1.6cm x 2.1cm and abnormal hormonal result, high prolactine, low cortisol and high IGF1. In Soetomo Hospital was diagnosed as pituitary macroadenoma with acromegaly and hyperprolactinemia and received bromocriptine 3x5 mg evaluated for 2 weeks then lowered to 3x 2.5 mg after obtaining a decrease in prolactin levels and methyl prednisolone 3x1 / day until cortisol level was normal. Patients will also plan for surgery of EETH (Endoscopic Endonasal Transphenoidal).